EXPLORING AND IDENTIFYING TECHNOLOGY-BASED DYNAMIC LEARNING THROUGH SOCIAL MEDIA IN ACADEMIC WRITING - Inderawati, Rita; Petrus, Ismail; Jaya, Hariswan Putra (Universitas Muhammadiyah Palembang, 2019)
Technology has been a new concept of learning in this digital era which brings positive response to students and lecturer. This current study focuses on the use of various social media that facilitate students to learn English. The aim of this research is to explore and to identify the use of Facebook in academic writing courses that perpetually developed to be a dynamic way of learning through a blended learning in terms of mobile learning. The 2nd semester students of 2017/2018 as the research subject who took Academic Paragraph Course. By utilizing mix-method through observation, documentation, questionnaire, and interview, this study explored and identified the language learning through social media. The result of the study was that the English learning especially academic writing could be categorized as a dynamic learning with exact rich connections in Facebook group account which was utilized both online and offline mode of learning with various learning models appropriate to the 21st century English learning where a dynamic interaction amongst lecturer and students happened by collaborating, communicating, thinking critically, and creating through self/peer assessment and a series of dynamic learning.